PENGARUH BOBOT UMBI PADA PERKECAMBAHAN BAWANG MERAH (ALLIUM ASCOLANICUM L) VAR. BIMA - Eka Baluwo; Jelly Porong; Tommy Ogie (Universitas Sam Ratulangi, 2021)
ABSTRAKThe shallot plant (Allium ascalonicum L.) is one of the annual species included in the Liliaceaefamily. Onion production in North Sulawesi from 2013 to 2017, namely; 1,354 tons, 1,242tons, 1,716 tons, 2,556 tons and 2,880 tons. Production of shallots in Indonesia in 2016amounted to 1,446,869 tons and in 2017 an increase of 1,470,155 tons (Central StatisticsAgency, 2019). Consumption of shallots in Indonesia is 4.56 kg / capita per year or 0.38 kg /capita per month, so that the national consumption is estimated to reach 1,608,000 tons peryear. Vegetative shallot seeds (pseudo tubers) have a high moisture content, so they need anappropriate storage process in order to maintain viability during storage. This study aims toobtain the ideal tuber weight for the seeds of the shallot plant. To get the ideal tuber weight forseeds from onion plants. To get the ideal tuber weight for seeds from onion plants. This researchwas prepared using a randomized block design (RAK) with the treatment of seed weight on thetubers and each treatment was repeated three times A = 2-3 gr, B = 4-5 gr, C = 6-7 gr, D = 8-9 gr and E = â‰¥ 10 gr. Each treatment consisted of 20 plant samples and was repeated 3 times,so that a total of 300 plants were obtained. The results of the research conducted, it can beconcluded that treatment A (2-3gr) is the ideal seed weight for the germination process, boththe speed of germination and the synchronization of sprouts followed by treatment B, C, andD.Kata Kunci: Bobot Umbi Bawang Merah